Repair of megameatus: A modified approach. Issue 2 (April 2015) - Faasse, M.A.; Dray, E.V.; Cheng, E.Y.
Summary Objective To demonstrate surgical reconstruction of a megameatus variant of hypospadias by using a modified, patient-specific approach. Methods An 8-month-old male had a megameatus, which was discovered after newborn circumcision. In repair of megameatus, it is important to recognize the full extent to which the distal urethra is widened, in order to avoid inadvertent urethrotomy during mobilization of the glans wings and skin immediately proximal to the glans. In this case, a small wedge of tissue was excised from the ventral aspect of the urethra, and a midline relaxing incision of the urethral plate was made. Standard principles of hypospadias repair should be followed, with tension-free urethral tubularization, coverage of the neourethra with well-vascularized tissue, and adequate mobilization of the glans wings to allow midline reconstruction without compression of the underlying neourethra. Results There were no perioperative or postoperative complications in this case. The urethral meatus was positioned near the tip of the glans penis, and there was no evidence of meatal stenosis or urethrocutaneous fistula at 5-months follow-up. Conclusion Each case of megameatus is unique, and a variety of surgical techniques can be used in formulating an approach that achieves optimal cosmetic and functional outcomes.